SYNTHESIS AND EVALUATION OF SOME NEW THIADIAZOLES AS ANTIMICROBIAL AGENTS - AMGOTH SRINIVAS NAYAK (International Journal of Pharma and Bio Sciences, 2014)
A new series of 2,5-disubstituted 1,3,4-thiadiazoles were synthesized by using different aromatic or aliphatic carboxylic acids (1) and thiosemicarbazide (2). The structures of the synthesized compounds were established by their spectral (IR, 1H NMR and Mass) data. All the compounds were screened for their antimicrobial activity against Staphylococcus aureus. Escherichia coli, Compounds showed mild to moderate activity, but not comparable with the standard (Norflaxacin).